Development of Tahsin Al-Qur’an E-module for high school students - Maywandang, Fadhiil Nabhaan; Lisnawati, Santi (Tawazun: Jurnal Pendidikan Islam, 2026)
The Qur’an as a guide for Muslims should be a reference and even daily reading, especially in Indonesia, which has a Muslim majority. However, there are still many students who are unable to read it properly. Therefore, one of the efforts needed is the development of a digital-based Tahsin E-Module as a solution to make learning easier and more effective. The purpose of this study is to analyze the need for e-module development, develop the e-module itself, and test the feasibility of the E-module Tahsin Qur’an for high school students. The research used the ADDIE R&D model method, which includes the stages of needs analysis through literature study, observation, and interviews, systematic and interesting material design, expert development and validation, implementation to teachers and students, and evaluation for product refinement. The result is a practical, systematic E-Module for Tahsin Al-Qur’an that can be accessed at any time, assists in the teaching, talaqqi, and murajaah processes, and serves as enrichment material for PAI with material on the rights and obligations of letters, waqf, and gharib. Based on the feasibility test, the module obtained an average validation score of 91.375% with a “highly feasible” category, making it effective and ready for use in learning. Abstrak Al-Qur’an sebagai pedoman hidup muslim seharusnya menjadi rujukan bahkan bacaan harian, terutama di Indonesia yang mayoritas muslim, namun nyatanya masih banyak siswa yang belum mampu membacanya dengan baik sehingga salah satu upaya diantaranya diperlukan pengembangan E-Modul Tahsin berbasis digital sebagai salah satu solusi agar pembelajaran lebih mudah dan efektif, adapun tujuan daripada penelitian ini ialah untuk menganalisis kebutuhan pengembangan e-modul beserta mengembangkan e-modul itu sendiri dan untuk menguji kelayakan E-modul tahsin Qur’an untuk siswa tingkat SMA. Penelitian menggunakan metode R&D model ADDIE yang meliputi tahap analisis kebutuhan melalui studi pustaka, observasi, dan wawancara, perancangan materi yang sistematis dan menarik, pengembangan serta validasi ahli, implementasi kepada guru dan siswa, hingga evaluasi untuk penyempurnaan produk. Hasilnya berupa E-Modul Tahsin Al-Qur’an yang praktis, sistematis, dapat diakses kapan saja, membantu proses mengajar, talaqqi, dan murajaah, serta berfungsi sebagai bahan pengayaan PAI dengan materi hak dan mustahak huruf, wakaf, dan gharib. Berdasarkan uji kelayakan, modul memperoleh rata-rata nilai validasi 91,375% dengan kategori “sangat layak”, sehingga dinilai efektif dan siap digunakan dalam pembelajaran.